Beyond the Trees: A Systems Approach to Understanding Forest Health in the Southeastern United States - Geetha S. Iyer; Martha C. Monroe; Jason A. Smith (EDIS)
Forest health is an important topic for biology, agriculture, current issues, and environmental science classes. But conversations with educators suggested that they were not equipped to teach about it given their existing curricula. This 79-page educator guide includes six activities designed to help learners consider forest health from various viewpoints; understand interrelationships and feedback mechanisms in a forest system; visualize spatial and temporal mechanisms of forest system functions; appreciate the variety of threats to forest health; and consider their role as future forest stewards. Written by Geetha S. Iyer, Martha M. Monroe, and Jason A. Smith, and published by the UF Department of School of Forest Resources and Conservation, July 2011.